2007
DOI: 10.1161/hypertensionaha.106.085175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nocturnal Nasal Continuous Positive Airway Pressure on Blood Pressure in Obstructive Sleep Apnea

Abstract: Abstract-Obstructive sleep apnea (OSA) is a very common risk factor for hypertension, and continuous positive airway pressure (CPAP) has been widely used to treat OSA. We conducted a meta-analysis of randomized, controlled trials to evaluate the effects of CPAP on blood pressure, reported as either a primary or secondary end point, among patients with OSA. Studies were retrieved by searching Medline (January 1980 to July 2006), the Cochrane Database of Systematic Reviews, conference abstracts, and bibliographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
272
4
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(304 citation statements)
references
References 41 publications
10
272
4
18
Order By: Relevance
“…Because it provides symptom relief, CPAP therapy is first‐line therapy for SA, but could theoretically also reduce the negative cardiovascular impacts of SA as it has been found to improve glucose tolerance, reduce endothelial damage, lower blood pressure, and improve cardiac function 6, 7, 8, 9, 10. Consequently, one could hypothesize that CPAP therapy protects patients from developing cardiovascular disease such as HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it provides symptom relief, CPAP therapy is first‐line therapy for SA, but could theoretically also reduce the negative cardiovascular impacts of SA as it has been found to improve glucose tolerance, reduce endothelial damage, lower blood pressure, and improve cardiac function 6, 7, 8, 9, 10. Consequently, one could hypothesize that CPAP therapy protects patients from developing cardiovascular disease such as HF.…”
Section: Discussionmentioning
confidence: 99%
“…One study even found an increased risk of incident HF among men with obstructive sleep apnea (OSA) 5. Continuous positive airway pressure (CPAP) therapy is a documented treatment for SA because of symptom relief, but it may also reduce endothelial damage and improve blood pressure, glucose tolerance, and cardiac function in patients with HF 6, 7, 8, 9, 10. However, a direct beneficial effect of CPAP therapy on cardiovascular outcomes has never been established in a controlled setting 11, 12.…”
mentioning
confidence: 99%
“…Summarizing these findings, a systematic review 61 and four meta-analyses [62][63][64][65] assessing the impact of CPAP on blood pressure have been published in the past few years. All point to a blood pressure reduction with the use of CPAP.…”
Section: Treatmentmentioning
confidence: 99%
“…In Haentjens et al's study 63 , which analyzed 12 placebocontrolled trials using ABPM for the assessment of blood pressure, there was a reduction by 1.77 and 1.79 mmHg in the mean 24-hour systolic and diastolic blood pressures, respectively. The most recent meta-analysis evaluated 818 patients and showed a reduction by 2.46 mmHg in systolic blood pressure and by 1.83 in diastolic blood pressure after the use of CPAP 65 . We should point out that these levels of blood pressure reduction can account for a long-term reduction of cardiovascular events.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation